Enzyme immunoassay for diagnosis of gonorrhea. - Schachter, J (1984)
An enzyme immunoassay (EIA; Gonozyme [Abbott Laboratories]) for gonococcal antigen was assessed for the rapid diagnosis of gonorrhea. Patients attending two sexually transmitted disease clinics were tested by EIA and culture on Thayer-Martin medium. EIA was highly effective in detecting gonococcal infection among symptomatic men, with 70 of 75 (93.3%) culture-positive men having positive tests and no false-positive reactions. The performance of the test was not as good in detecting cervical gonorrhea; the best result obtained was a sensitivity of 87% (33 of 38) for EIA compared with culture. EIA false-positives occurred at a relatively low rate for women, with the test having a specificity of ca. 97%. The test clearly is capable of detecting gonococcal antigen in cervical and urethral specimens, but its role in routine diagnosis is not clear. Its performance seems equal to that of the Gram stain for men, but it seems to be less sensitive than culture for cervical gonorrhea--a drawback in high-risk populations. The low false-positive rate could be an important issue in screening low-prevalence populations.